Could homocysteine represent a negative acute phase reactant in canine infections-a pilot study? - Ilic Bozovic, A; Đoković, P; Milanović, Z; Janjić, F; Spariosu, K; Radonjić, V; Radaković, M; Magaš, V; Filipović, D; Stanković, S; Kovačević Filipović, M; Beletić, A (Journal of the Hellenic Veterinary Medical Society, 2023)
Homocysteine (Hcy) was investigated as the biomarker of cardiac, renal, and gastrointestinal disorders in dogs. Data about low Hcy concentrations in the systemic inflammatory response syndrome raised a hypothesis that Hcy in dogs is a negative acute-phase reactant. This survey compared Hcy concentrations, serum amyloid A (SAA), and the routine laboratory parameters between healthy (HD, N=6) and dogs with inflammation of different extent: mild ( dirofilariosis (DIR), N=31), moderate (babesiosis (BAB), N=12), and severe (pyometra (PYO), N=8). The BAB and PYO groups had lower Hcy er than HD. Also, the levels in the PYO group were below those in the DIRO group. SAA had the inverse pattern. Across the groups, Hcy and SAA levels correlated negatively (ρ = -0.502, P<0.001). Hcy and SAA correlated with the erythrocyte count, hematocrit, hemoglobin and mean cellular hemoglobin concentrations, and neutrophil count, with correlations being positive for Hcy and negative for SAA. Among all dogs, hemoglobin was the only independent predictor of Hcy concentration. Hcy levels in canine infections, decreased as acute-phase reaction (APR) intensified. Also, they were related with the hematology changes accompanying the APR. Further studies will establish the clinical potential of these alterations.